"Semicut” skill on the cystic duct in laparoscopic cholecystectomy - Liu, Linxun; Zhao, Zhanxue; Yang, Jinyu (Frontiers in Surgery, 2023)
Abstract Objective: The aim of this study was to decrease the incidence of residual stones in the cystic duct and to consequently decrease the incidences of intractable pain and the formation of a small gallbladder after laparoscopic cholecystectomy (LC). Methods: We changed the order of the clamps when we performed LC, then used the “semicut" skill of the cystic duct, and removed the stones residing in the cystic duct. Results: 45 patients underwent the operation, and all of the operations were successfully completed. This technique did not increase the operation time or difficulty. Conclusions: The "semicut" skill of the cystic duct is a safe and feasible surgical method that may change the occurrence of intractable pain after LC.